Engineering fundamentals : an introduction to engineering - Moaveni, Saeed (Singapore : Cengage Learning Asia Pte Ltd, 2019)
This text helps readers develop the strong problem-solving skills and solid foundation in fundamental principles they will need to become analytical, detail-oriented, and creative engineers. The book opens with an overview of what engineers do, an inside glimpse of the various areas of specialization, and a straightforward look at what it takes to succeed. The book then covers the basic physical concepts and laws that you'll encounter on the job. Professional Profiles throughout the text highlight the work of practicing engineers from around the globe, tying in the fundamental principles and applying them to professional engineering. Using a flexible modular format, the book demonstrates how engineers apply physical and chemical laws and principles, as well as mathematics, to design, test, and supervise the production of millions of parts, products, and services that people use every day.
Part 1: Engineering -- 1. Introduction to the engineering profession -- 2. Preparing for an engineering career -- 3. Introduction to engineering design -- 4. Engineering communication -- 5. Engineering ethics -- Part 2: Engineering Fundamentals -- 6. Fundamental dimensions and units -- 7. Length and length-related variables in engineering -- 8. Time and time-related variables in engineering -- 9. Mass and mass-related variables in engineering -- 10. Force and force-related variables in engineering -- 11. Temperature and temperature-related variables in engineering -- 12. Electric current and related variables in engineering -- 13. Energy and power -- Part 3: Computational Engineering Tools -- 14. Computational engineering tools electronic spreadsheets -- 15. Computational engineering tools MATLAB -- Part 4: Engineering Graphical Communication -- 16. Engineering drawings and symbols -- Part 5: Engineering Material Selection -- 17. Engineering materials -- Part 6: Mathematics, Statistics, and Engineering Economics -- 18. Mathematics in engineering -- 19. Probability and statistics in engineering -- 20. Engineering economics -- Appendix.
Includes index.
Keywords: ENGINEERING